Issues on clinical application of hypoxia-inducible factor prolyl hydroxylase inhibitor Roxadustat - TU Yan; ZHANG Xiao-liang (Linchuang shenzangbing zazhi)
Renal anemia is an important clinical manifestation of chronic kidney disease.The relative or absolute deficiency of erythropoietin(EPO) is the main cause of renal anemia.At present,renal anemia is treated mainly with EPO analogues combined with ferralia.However,its clinical application is limited due to its side effects.Hypoxia-inducible factor(HIF) is a transcription factor regulating EPO gene expression.Prolyl hydroxylase is the rate limiting enzyme that regulates the degradation of HIF.Prolyl hydroxylase inhibitor(PHI) can stabilize HIF and promote EPO expression.As the first HIF-PHI in the world,roxadustat has first completed phase III clinical trials and been approved for marketing in China.At present,most of its medication experience comes from phase III clinical trials in China.Therefore,most clinicians lack the long-term medication experience of roxadustat.Therefore,we briefly summarize some issues on the clinical application of roxadustat in this paper for clinicians’ reference.